The tabanid fauna (Diptera: Tabanidae) of the Chirpan Eminences (Bulgaria) - Ganeva, Diana; Kalmushka, Milena (ENTOMOLOGIA HELLENICA, 2012)
The study of the Chirpan Eminences tabanid fauna was completed by means of a route collection in 2008 and regular monthly collections from two localities during the active tabanid sea-sons in years 2010-2011. The research resulted in the capturing of 1202 tabanid specimens, 1124 of them were females and 78 males. Within this collected sample 24 species and subspecies from 8 genera were determined: Chrysops (2 species), Atylotus (1 species), Therioplectes (1 species and 1 subspecies), Hybomitra (3 species), Tabanus (12 species and 1 subspecies), Haematopota (1 species), Dasyrhamphis (1 species) and Philipomyia (1 species). On the basis of literary data and of the species identified in this research, it may be asserted that the tabanid fauna in the Chirpan Eminences is represented by 28 species. Thirteen of them were identified for the first time for this region. From a zoogeographical point of view, predominant for the tabanid fauna of the Chirpan Eminences are the elements of the Mediterranean subregional fauna (64.29 % of the species).